Capitalism and religion : the price of piety - Goodchild, Philip, 1965- (Routledge, 2002)
Condemns modernity and capitalism as a global religion. Presents a philosophical alternative that demands attention from philosophers, critical theorists, philosophers of religion, theologians and those in ecological politics.